Sosialisasi Transformasi Literasi Pajak Penghasilan Bagi Generasi Milenial Melalui Pendekatan Komunikatif Dan Digital - Syafrul Antoni; Alan Rakhmat Putra; M Karim; Karlini Oktarina (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve tax literacy, particularly Income Tax (PPh), among the millennial generation in Sungai Penuh City. The activity was carried out in four stages, namely: preparation and planning, implementation of socialization, simulation and Q&A, and evaluation. In the preparation stage, information needs were identified which resulted in visual and digital-based educational modules and media. The socialization was carried out face-to-face and online with a communicative approach relevant to the characteristics of the younger generation. Tax calculation and reporting simulations were conducted to improve participants' practical understanding, followed by an interactive Q&A session. Evaluation using pre-test and post-test methods showed a significant increase in participants' understanding, from an average score of 52 to 84. This activity also received a positive response from participants, with the majority feeling more confident in fulfilling their tax obligations independently. These results indicate that a communicative and applicable educational approach is effective in encouraging voluntary tax compliance among millennials.